Relationship of Brand Ambassadors with Interest to Buy: Lazada e-Commerce Study - Netti Natarida Marpaung (Jurnal Office, 2021)
This research aims to determine and analyze the influence of Brand Ambassador on Buying Interest at Lazada. This study uses quantitative methods. The variables that are connected in this study are Brand Ambassador (X) and Purchase Interest (Y). Sources of data used consist of primary data, population observations and samples in this study are consumers. The test was carried out using the help of SPSS 26. The results obtained from this research indicate that partially brand ambassadors have a positive and significant effect on buying interest at Lazada. Brand ambassador variable has a strong influence. The Adjusted R-Square value obtained is 0.489. It can be said that the contribution of the brand ambassador to the purchase intention variable is significant